Oral-to-rectum microbial transmission in orthopedic patients without a history of intestinal disorders - Lin, Ge; Kageyama, Shinya; Maeda, Aiko; Sakamoto, Eiji; Ma, Jiale; Asakawa, Mikari; Furuta, Michiko; Yamashita, Yoshihisa; Takeshita, Toru (Frontiers in Cellular and Infection Microbiology, 2024)
The enrichment of oral taxa in the gut has recently been reported as a notable alteration in the microbial balance in patients with intestinal disorders. However, translocation in populations without such diseases remains controversial. In this study, we examined 49 pairs of tongue and rectal samples collected from orthopedic patients without a history of intestinal disorders to verify the presence of oral taxa in the rectal microbiota. The bacterial composition of each sample was determined using 16S rRNA gene sequencing and amplicon sequence variant (ASV) analysis. Although the bacterial compositions of the tongue and rectal microbiota were distinctly different, tongue ASVs were detected in 67.3% of the participants and accounted for 0.0%–9.37% of the rectal microbiota. Particularly, Streptococcus salivarius, Fusobacterium nucleatum, and Streptococcus parasanguinis were abundant in the rectal microbiota. According to the network analysis, tongue taxa, such as S. salivarius and S. parasanguinis, formed a cohabiting group with Klebsiella pneumoniae and Alistipes finegoldii in the rectal microbiota. The total abundance of tongue ASVs in the rectal microbiota was significantly higher in participants with older age, hypertension, and proton pump inhibitor (PPI) use. Our study presents an extensive translocation of oral taxa to the rectum of a population without intestinal disorders and suggests that aging, hypertension, and PPI use are associated with an increased abundance of oral taxa and potential pathogenic bacteria in the rectal microbiota.